WS2/Graphitic Carbon Nitride Heterojunction Nanosheets Decorated with CdS Quantum Dots for Photocatalytic Hydrogen Production. Issue 7 (9th March 2018) - Zou, Yajun; Shi, Jian‐Wen; Ma, Dandan; Fan, Zhaoyang; Cheng, Linhao; Sun, Diankun; Wang, Zeyan; Niu, Chunming
Abstract: Two‐dimensional/two‐dimensional (2D/2D) stacking heterostructures are highly desirable in fabricating efficient photocatalysts because face‐to‐face contact can provide a maximized interfacial region between the two semiconductors; this largely facilitates the migration of charge carriers. Herein, a WS2 /graphitic carbon nitride (CN) 2D/2D nanosheet heterostructure decorated with CdS quantum dots (QDs) has been designed, for the first time. Optimized CdS/WS2 /CN without another cocatalyst exhibits a significantly enhanced photocatalytic H2 evolution rate of 1174.5 μmol h −1  g −1 under visible‐light irradiation ( λ >420 nm), which is nearly 67 times higher than that of the pure CN nanosheets. The improved photocatalytic activity can be primarily attributed to the highly efficient charge‐transfer pathways built among the three components, which effectively accelerate the separation and transfer of photogenerated electrons and holes, and thus, inhibit their recombination. Moreover, the extended light‐absorption range also contributes to excellent photocatalytic efficiency. In addition, the CdS/WS2 /CN photocatalyst shows excellent stability and reusability without apparent decay in the photocatalytic H2 evolution within 4 cycles in 20 h. It is believed that this work may shed light on specifically designed 2D/2D nanosheet heterostructures for more efficient visible‐light‐driven photocatalysts. Abstract : Sheets gone dotty : Efficient photocatalysts for hydrogen production through water splitting have been achieved by decorating WS2 /graphitic carbon nitride (CN) 2D/2D nanosheets with CdS quantum dots. The improved photocatalytic activity can be attributed to the highly efficient charge‐transfer pathways built among the three components.